2022
DOI: 10.3390/healthcare10060975
|View full text |Cite
|
Sign up to set email alerts
|

Post-Pandemic Stress Disorder as an Effect of the Epidemiological Situation Related to the COVID-19 Pandemic

Abstract: According to many experts in the fields of psychology and psychiatry, the destabilization resulting from the coronavirus pandemic may not be as noticeable now as it will be after the pandemic period is over. Undoubtedly, the fact that the surrounding reality is standardized and normalized by many at present contributes to this. In the opinion of many researchers, the scale and degree of trauma experienced by society will only be noticed by many once the pandemic is over. Many also suggest that we will experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Our research suggests that individuals with lower levels of executive functions might be exposed to a heightened risk of COVID-19 stress and its detrimental effects (Hatun & Kurtça, 2022 ; Passavanti et al, 2021 ; Madison et al, 2021 ), pointing to the necessity of targeted interventions (Holmes et al, 2020 ). This is especially critical in the current post-pandemic stage, given that the prevalence of mental health disorders such as post-pandemic stress disorder is expected to rise as a result of the pandemic’s long-term effects (Kathirvel, 2020 ; Łaskawiec et al, 2022 ; Tandon 2020 ; Taylor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research suggests that individuals with lower levels of executive functions might be exposed to a heightened risk of COVID-19 stress and its detrimental effects (Hatun & Kurtça, 2022 ; Passavanti et al, 2021 ; Madison et al, 2021 ), pointing to the necessity of targeted interventions (Holmes et al, 2020 ). This is especially critical in the current post-pandemic stage, given that the prevalence of mental health disorders such as post-pandemic stress disorder is expected to rise as a result of the pandemic’s long-term effects (Kathirvel, 2020 ; Łaskawiec et al, 2022 ; Tandon 2020 ; Taylor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased attention to studying the prevalence of COVID-19 stress (e.g., Mahmud et al, 2021 ; Salari et al, 2020 ), few studies have identified risk factors that could inform targeted interventions. Protecting populations against the psychological effects of COVID-19 remains highly relevant during the post-pandemic period not solely because pandemics are far from once-in-a-lifetime events (Taylor, 2022 ), but also because the prevalence of mental health disorders is expected to rise over time with the pandemic’s long-term ramifications (Colizzi et al, 2022 ; Kathirvel, 2020 ; Łaskawiec et al, 2022 ; Tandon, 2020 ; Taylor et al, 2020 ). These include, but are not limited to, the pandemic’s effects on the economy, social relationships and individual health (Łaskawiec et al, 2022 ).…”
mentioning
confidence: 99%
“…Indeed, finding the cause of such symptoms is more important than trying to deal with the symptoms alone. Otherwise, the symptoms will recur and people constantly might experience a condition so-called a state of danger [ 12 ]. Thus, assessing phobia in this period seems essential.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted the correlation between increased fear and anxiety towards COVID-19 and psychophysical deterioration [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. It is also worth mentioning that some WHO reports indicate the existence of symptoms similar to post-traumatic stress disorder in the population [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%